Taylor rule in Brazil - Bueno, Rodrigo de Losso da Silveira (2005)
In this paper, we use the Taylor Rule to characterize empirically the Brazilian monetary policy before and after its major and succesful stabilization plan, Real Plan, launched in 1994. Specifically, we show how the inflation coefficient has changed after the stabilization plan was carried out. This is a natural experiment to test theories surrounding the Taylor Rule in which monetary instability is characterized by an inflation coefficient less than one, whereas monetary stability will have a greater than one coefficient (seeWoodford’s (2003)). Very suprisingly the paper shows that the inflation coefficient has remained less than one even after the stabilization. Our results are quite robust with respect to different samples, lags of variables, proxies for GDP, proxies for potential GDP and even with respect to econometric methods (see Bueno (2005a, 2005b)). The implications are very important both theoretically and empirically. First, it shows some gap in theory that deserves further investigation. Second, it suggests that the inflation targeting regime has been uneffective in Brazil confirming a feeling largerly spread among Brazilians.